Evidências empíricas de um modelo teórico para explicar a noopsicossomática em pessoas vivendo com HIV/AIDS - Pontes, Alisson de Meneses (2012)
AIDS is a disease caused by HIV, which destroys the defense mechanisms of the human body because it has as main target immune system cells (CD4+). However, with the emergence of Antiretroviral Therapy, HIV/AIDS was classified as a chronic disease, which improved the quality of life of its bearer and included in their studies variables such as religiosity / spirituality, the meaning of life and affections. In this perspective, this research aimed to test a theoretical model proposed by Viktor Frankl explains the dynamics of noopsychosomatic in people living with HIV/AIDS. Specifically, we sought to understand how the size noological (represented by the religious attitude and sense of accomplishment), influences the psychic dimension (positive affect and the perception of the past) and thus affects the somatic dimension (represented by the functioning of the immune system through the level of CD4+/CD8+). Thus, 115 participants were seropositive for HIV / AIDS, aged 18-63 years (sd = 10.32 m = 39), and 61.37% male. The patients answered a set of five instruments: Sense of Life Questionnaire; Scale Ontological Perception of Time, Scale Positive and Negative Affects; Religious Attitude Scale Questionnaire and a socio-demographic and clinical. Analyzes were performed descriptive, bivariate - Pearson correlations (r) - and factorials. Through AMOS (version 7) proceeded with a path analysis (path analysis) to test the theoretical prediction of the indices represented by the ratio of lymphocytes CD4+/CD8+. The results indicate that suitability model, with rates adjustments plausible: χ2 (20) = 27.4 (p <0.01); χ2/gl = 1.37, GFI = 0.95, AGFI = 0.91 ; = CFI RMSEA = 0.97 and 0.06 (90% CI = from 0.000 to 0.11); pclose test indicated that the value of RMSEA is taken as statistically higher than the cutting point, ie 0.05 . It is worth noting that all saturations (the lambda, λ) were statistically different from zero (z> 1.96, p <0.05). The results showed that the religious attitude - composed of the four factors: religious knowledge (λ = 0.87), religious behavior (λ = 0.87), religious sentiment (λ = 0.63) and religious embodiment (λ = 0 , 56) - was directly associated with the realization of meaning (λ = 0.37), which in turn was related to satisfaction with the past (λ = 0.35). Finally, the immune system, measured by CD4 + / CD8 +, was predicted by the same item (λ = 0.16). Thus, he conceives that this work brought together empirical evidence about the adequacy of the theoretical model of noopsychosomatic in patients living with HIV/AIDS. It is understandable, therefore, the relevance of religion/ spirituality and meaning of life in the process of illness and health.